Ser nascido na vida: a fenomenologia da vida de Michel Henry e sua contribuição para a clínica - Wondracek, Karin Hellen Kepler (2010)
This thesis investigates Michel Henry s contribution to the psychotherapeutic clinical practice. His very original phenomenology of Life deepens questions raised in the dialogue between Freund and Pfister. Part 1: Life, Work and Thinking of Michel Henry. His criticism of the directions of Western thought points to effects of Galilean reductionism on ontological monism, which only considers true what can be represented or seen. This is insufficient to the understanding of the human condition; Henry proposes the dualism of appearance and the inversion of the phenomenological method in order to encompass the phenomenalization of the life that donates itself as affection in immanence. Henry s most important contribution is his pioneering phenomenological investigation of the self-affectional condition of affection. Part II: Henry's journey through Christianity as a phenomenological proposal of access to the truth of Life: Christianity bestows a paradigm to Philosophy, which is still little explored, proposing the understanding of life in the intelligibility of the invisible Logos that generates everything visible. The Human condition is that of Son, born in the absolute Life; his life donated as a Self given in radical passivity. Through the phenomenology of incarnation the notion of pathos is deepened, with consequences for the issues of suffering and anguish. The Human condition is paradoxical in this articulation between visible and invisible truth. Part III: The Henryan reading of Psychoanalysis: Psychoanalysis shelters life amidst the barrenness of Western thought, but is also affected by it, even in its fundamental concepts, especially its approach to affection. As a counterpoint to genealogy as described by Henry, the Jewish rooting of Psychoanalysis is highlighted, which allows him to maintain the paradigm of non-representability and of errancy. With Julia Kristeva we point to the proximity with the affirmations of the Phenomenology of Christianity. In the end, we return to the clinical setting and to the contributions of Phenomenology of Life to the praxis, in the paradigm of the double appearance.